A soft cross-linked polyester resin film that exhibits self-adhesiveness, remoldability, and scratch repair properties

A crosslinked polyester resin film with ester bonds and free OH groups, using a transesterification catalyst, addresses flexibility, transparency, and strength issues, enabling remolding and scratch repair through bond exchange.

JP7613544B2Active Publication Date: 2025-01-15TOYOBO CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023210684
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-08-20
Filing Date
2023-12-14
Publication Date
2025-01-15
Estimated Expiration
2039-08-27

AI Technical Summary

Technical Problem

Existing polyester resin films lack flexibility, transparency, and strength while also being unable to be remolded or repaired from scratches, due to issues with covalent and physical crosslinking methods.

Method used

A crosslinked polyester resin film with a polymer main chain containing ester bonds and free OH groups, combined with a transesterification catalyst, allowing for bond exchange at high temperatures, enabling reprocessing and scratch repair.

Benefits of technology

The film exhibits high transparency, flexibility, and strength, with the ability to be remolded and repaired from scratches through dynamic covalent crosslinking, facilitating industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007613544000004
    Figure 0007613544000004
  • Figure 0007613544000005
    Figure 0007613544000005
  • Figure 0007613544000006
    Figure 0007613544000006
Patent Text Reader

Abstract

To provide: a crosslinked polyester resin excellent in terms of transparency, adhesive property, pliability (stretchability), and strength (Young's modulus) and further having re-formability and flaw-repairing properties; and a crosslinked-polyester-resin multilayer film including the crosslinked polyester resin in a film form.SOLUTION: There is provided a polyester resin 5 which comprises: a polymeric main chain 1 including ester bonds 2 at a large number of sites; and a large number of covalent crosslinking moieties 3 each including an ester bond 2 and a free OH group 4. The polyester resin 5 can be obtained by mixing a raw polyester-resin material including ester bonds 2 and carboxy groups at a large number of sites with both a diepoxy crosslinking agent and a transesterification catalyst 6 and heating the mixture to crosslink the polyester resin.SELECTED DRAWING: Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a soft crosslinked polyester resin film that exhibits self-adhesiveness, remoldability, and scratch repairability, as well as a soft multilayer crosslinked film and a method for producing the same. [Background technology]

[0002] Since the bond-exchange type dynamic covalent bond crosslinked film can bond films together without using adhesives, it can suppress the elution of foreign matter and residual solvents caused by adhesives, making it possible to produce a film with excellent safety.

[0003] Conventional covalently crosslinked films have poor reworkability and adhesiveness due to the irreversibility of the covalent crosslinking points. On the other hand, films with physical crosslinking (crosslinking by crystalline domains or glassy domains) can be reworked and adhered by heat, but have problems such as low water resistance, low solvent resistance, and low transparency.

[0004] In addition, conventional covalently crosslinked elastomers cannot be remolded or repaired due to the irreversibility of the covalent crosslinking points. On the other hand, elastomers with physical crosslinking (crosslinking by crystalline domains or glassy domains) can be remolded and surface scratches can be repaired by heat, but they have problems such as low water resistance, low solvent resistance, and low transparency.

[0005] Patent Document 1 describes a laminate produced by heating a polyester resin film and a polyolefin resin film, while Patent Document 2 describes a laminate having at least one layer of a polyester-based film.

[0006] The laminate in Patent Document 1 is heated mainly by electron beam irradiation, and since it contains a polyolefin resin film, it is inferior in transparency compared to a laminate of polyester resin films. On the other hand, the polyester film described in Patent Document 2 has poor flexibility and toughness at room temperature because the total amount of one or more monomer components that can become amorphous components is 12 mol % or more and 30 mol % or less among all monomer components. In addition, Non-Patent Document 1 describes a method for preparing a crosslinked material by introducing a bond exchange reaction, but does not describe the adhesive properties of a film-like sample.

[0007] Patent Document 3 describes that a self-repairing resin composition containing a polyester resin, an organic titanium compound, 1,4-butylene glycol, bis(2-hydroxyethyl) terephthalate, or dimethyl phthalate can recombine polymer chains to perform self-repair and prevent deterioration. However, the self-repair is evaluated based on the average molecular weight of the composition, and there is no description of damage sustained by the composition.

[0008] Patent Document 4 discloses a self-repairing resin body that is characterized by including an amorphous polymer X having a dangling chain and a crosslinked structure, and an amorphous polymer Y having a glass transition temperature of room temperature or higher as measured by dynamic viscoelasticity measurement. However, the evaluation of the damage caused to the self-repairing resin body is not clear, and there is no description of the remolding processability of the self-repairing resin body.

[0009] On the other hand, Non-Patent Document 1 does not describe the production of a bond exchange type dynamic covalent bond crosslinked film that exhibits flexibility at room temperature. In addition, there is no description of self-adhesiveness or repairability of surface scratches. In addition, Non-Patent Document 2 describes remoldability, but only shows an elongation rate of about 5%, and does not show properties as a soft resin. In addition, there is no description of repairability of surface scratches or self-adhesiveness. Non-Patent Document 3 describes the production of a bond exchange type dynamic covalent bond crosslinked film that contains a catalyst during crosslinking molding, but there is no description of the production of a bond exchange type dynamic covalent bond crosslinked film by immersing a non-catalyst-containing sample in a catalyst-containing solution. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] JP 2012-254593 A [Patent Document 2] Re-tabled publication No. 2014-175313 [Patent Document 3] JP 2005-023166 A [Patent Document 4] JP 2010-260979 A [Non-patent literature]

[0011] [Non-Patent Document 1] Damien Montarnal, M. Capelot, F. Tournilhac, Ludwik Leibler, Science, 2011, Vol. 334, Issue 6058, 965-968. [Non-Patent Document 2] Jacob P. Brutman, Paula A. Delgado, and Marc A. Hillmyer, ACS Macro Letters, 2014, Vol. 3, Issue 7, 607?610. [Non-Patent Document 3] Mikihiro Hayashi,et al.,Polymer Chemistry.10(16)2047-2056,2019. Summary of the Invention [Problem to be solved by the invention]

[0012] The object of the present invention is to provide a soft crosslinked polyester resin film, i.e., a soft crosslinked polyester resin film, which has excellent transparency, crosslinking, flexibility (extensibility), and strength (Young's modulus) and further has remoldability and scratch repairability, and further to provide a soft multilayer crosslinked polyester resin film, i.e., a soft multilayer crosslinked polyester film, in the form of a film. [Means for solving the problem]

[0013] (1) A polyester resin having a polymer backbone containing multiple ester bonds and multiple covalent cross-linking moieties containing ester bonds and free OH groups (i.e., a cross-linked polyester resin containing multiple free OH groups in its network structure), and a cross-linked polyester resin containing an ester exchange catalyst. (2) The crosslinked polyester resin according to (1) above is obtained by mixing a polyester resin raw material containing ester bonds and carboxylic acid groups at multiple points, a diepoxy crosslinking agent, and the transesterification catalyst, and heating the mixture to crosslink the mixture. (3) The crosslinked polyester resin according to (2), wherein the average molecular weight of the polyester resin raw material is 8000 or more, and the number of polyester bonds contained in the polyester resin raw material is 100 or more. The average molecular weight is a number average molecular weight. (4) The crosslinked polyester resin according to (2) or (3), wherein the ratio of carboxylic acid groups in the polyester resin raw material is 10 mol % to 50 mol % relative to the ester groups in the polyester resin raw material, and the ratio of carboxylic acid groups in the polyester resin raw material to epoxy groups in the diepoxy crosslinking agent in the crosslinking reaction (carboxylic acid groups:epoxy groups) is 1:0.5 to 1:1.5. (5) The crosslinked polyester resin according to any one of (2) to (4), wherein the molar ratio of the transesterification catalyst to the free OH groups in the network structure after crosslinking (free OH groups:transesterification catalyst) is 1:0.1 to 1:0.4. (6) A method for producing a crosslinked polyester resin, which is obtained by mixing a polyester resin raw material containing ester bonds and carboxylic acid groups at multiple points, a diepoxy crosslinking agent, and an ester exchange catalyst, and heating the mixture to crosslink the mixture. (7) The crosslinked polyester resin is a crosslinked polyester resin according to any one of (1) to (5) above, which is in the form of a film. (8) A multi-layer crosslinked polyester resin film including a portion in which the film-shaped crosslinked polyester resin described in (7) is bonded and laminated. (9) A packaging material, characterized in that the multi-layer crosslinked polyester crosslinked resin film according to (8) is used at least in part. (10) A method for producing a multi-layer crosslinked polyester resin film, comprising pressing at least a part of the film-shaped crosslinked polyester resin according to (7) under high temperature. (11) A method for producing a remolded crosslinked polyester resin, comprising a deformation step in which the crosslinked polyester resin according to (7) is deformed in terms of its shape, and a heat treatment step in which the crosslinked polyester resin is subsequently treated with heat. (12) A method for producing a crosslinked polyester resin having repaired scratches, comprising the steps of: inflicting scratches on the surface of the crosslinked polyester resin according to (7); and then subjecting the crosslinked polyester resin to a heat treatment process. (13) A method for producing a crosslinked polyester resin, comprising mixing a polyester resin raw material containing ester bonds and carboxylic acid groups at multiple points with a diepoxy crosslinking agent, and heating the mixture to crosslink the resulting crosslinked polyester resin, and then immersing the resulting crosslinked polyester resin, which does not contain a transesterification catalyst, in a solution containing the transesterification catalyst. Effect of the Invention

[0014] The crosslinked polyester resin of the present invention has high transparency, and due to the "dynamic" covalent crosslinking that allows bond exchange at high temperatures, it has high strength and flexibility at room temperature, and can be reprocessed and bonded to films at or near the bond exchange activation temperature. In addition, the bond exchange catalyst used in the present invention is inexpensive, many types of catalysts are available, and the crosslinking reaction itself is short, making it convenient for industrialization. Furthermore, the remoldability of the crosslinked polyester resin allows for free shape adjustment and thinning after the crosslinking reaction, and its scratch repairability allows for semi-permanent use. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 is a schematic diagram showing a crosslinked polyester resin according to one embodiment of the present invention. [Diagram 2] This is a diagram showing a square cross-linked polyester resin molding (4 cm x 4 cm, thickness 0.1 cm). [Diagram 3] FIG. 1 is a diagram showing an example of a combination of raw materials for producing a crosslinked polyester resin, showing (A) a polyester resin raw material containing multiple carboxylic acid groups, (B) a diepoxy crosslinking agent, and (C) an ester exchange catalyst. [Figure 4] FIG. 2A is a schematic diagram showing an embodiment in which two crosslinked polyester resin films are laminated to form a two-layer crosslinked polyester resin film (B). FIG. [Diagram 5] FIG. 2 is a schematic diagram showing a polyester exchange reaction between crosslinked polyester resins, (A) before the reaction, and (B) after the reaction. [Figure 6] FIG. 1 is a diagram showing the structural formula of a polyester resin raw material obtained by melt condensation polymerization of adipic acid, thiomalic acid, and pentanediol. [Figure 7] FIG. 13 is a diagram showing an example of a chart for the definition of maximum stress and breaking elongation using Example 3. [Figure 8] FIG. 2A is a diagram showing a state in which two cross-linked polyester resin films are partially overlapped, and FIG. 2B is a diagram showing a state in which one cross-linked polyester resin film is bent. [Figure 9] FIG. 2A is a diagram showing a two-layer crosslinked polyester resin film bonded by pressing at a high temperature, and FIG. 2B is a diagram showing a two-layer crosslinked polyester resin film with a portion broken. [Figure 10]FIG. 1 is a diagram showing how to determine the softening temperature of crosslinked polyester resin films (Examples 4 to 6). [Figure 11] FIG. 2 is a diagram showing a crosslinked polyester resin film. [Figure 12] 1A and 1B are diagrams showing a crosslinked polyester resin film wrapped around a spatula with both ends fixed to the spatula, and (B) a crosslinked polyester resin film remolded by (A). [Figure 13] FIG. 2A is a diagram showing the surface of a cross-linked polyester resin film containing scratches (enlarged view), and FIG. 2B is a diagram showing the surface of a cross-linked polyester resin film from which the scratches have disappeared after a heat treatment process has been performed on (A) (enlarged view). [Figure 14] FIG. 1 is a schematic diagram of a method for producing a crosslinked polyester resin by immersing a crosslinked polyester resin (molded product) that does not contain a transesterification catalyst in a solution containing a transesterification catalyst. [Figure 15] FIG. 1 shows the results of linear expansion coefficient measurement for a crosslinked polyester resin (film) not containing an ester exchange catalyst immersed in a solution containing 0 (no catalyst), 2.5 mg / mL, 5 mg / mL, or 10 mg / mL of an ester exchange catalyst (zinc acetate). [Figure 16] FIG. 1 is a graph showing the softening temperature of a crosslinked polyester resin (film) not containing an ester exchange catalyst immersed in a solution containing an ester exchange catalyst (zinc acetate) at 2.5 mg / mL, 5 mg / mL, or 10 mg / mL. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, the embodiments of the present invention will be described with reference to the drawings. The present invention is not limited to the following embodiments, and changes, modifications, and improvements can be made without departing from the scope of the invention.

[0017] As shown in FIG. 1, the crosslinked polyester resin (7) of the present invention includes a polymer main chain (1) containing ester bonds (2) at multiple points, a polyester resin (5) containing multiple covalent crosslinking moieties (3) containing ester bonds (2) and free OH groups (4), and an ester exchange catalyst (6). The free OH group (free hydroxyl group) (4) is a hydroxyl group that is not contained in the ester bond (2) of the polymer main chain (1) and has not reacted with any functional group. The crosslinked polyester resin containing free OH groups at multiple points in the network structure means that the polymer main chain (1) contains ester bonds at multiple points and the covalent crosslinking moieties (3) contain free OH groups (4) at multiple points, i.e., the free OH groups (4) are partially contained in the polymer crosslinked network. As described later, a free OH group (4) attacks the C-0 bond of one of the many ester bonds in the vicinity through the action of a nearby ester exchange catalyst (6), causing an ester exchange reaction. When this ester exchange reaction progresses between the opposing surfaces of two overlapping films under high temperature and pressure, adhesion occurs through the new bonds that are generated.

[0018] The average molecular weight of the polyester resin raw material is preferably 8000 (g / mol) or more, more preferably 15000 (g / mol) or more, from the viewpoint of strength and heat resistance of the resin, and the number of ester bonds is preferably 100 or more, more preferably 200 or more, in order to achieve the above molecular weight.

[0019] The ratio of free OH groups is preferably 10 mol% to 50 mol%, more preferably 15 mol% to 40 mol%, based on the ester groups in the polyester resin raw material (polymer) from the viewpoints of ease of synthesis of polymer samples and flexibility at room temperature. The ratio of the transesterification catalyst is preferably 10 mol% to 40 mol%, more preferably 15 mol% to 30 mol%, based on the free hydroxyl groups from the viewpoints of mechanical strength of the resin and uniformity of the sample.

[0020] Molded products made from cross-linked polyester resin were transparent. Molded product (8) in Figure 2 was a square (4 cm x 4 cm, 0.1 cm thick), and even when placed on a piece of white paper with "NI tech" written in black, the letters "NI tech" looked just as clear as in the area where molded product (8) was not placed.

[0021] An example of a method for producing a crosslinked polyester resin (7) will be described with reference to Fig. 3. A diepoxy crosslinking agent (B) was mixed with a liquid polyester resin raw material (A) containing multiple carboxylic acid groups, and a transesterification catalyst (C) was added to carry out a crosslinking reaction via an epoxy ring-opening reaction.

[0022] The polyester resin raw material (A) is preferably a polyester containing carboxylic acid groups at multiple points. As the constituent monomers of the polyester that is the precursor of the polyester resin raw material (A), 1,5-pentanediol or 1,6-hexanediol is preferably used as a diol molecule, adipic acid or glutaric acid is preferably used as a dicarboxylic acid molecule containing a reactive group in the side chain, and thiomalic acid is preferably used as a dicarboxylic acid molecule containing a reactive group in the side chain. In this case, a polyester precursor containing thiol groups at multiple points in the side chain is obtained by melt polycondensation. When the precursor is reacted with, for example, acrylic acid, a polyester resin raw material (A) containing carboxylic acid at multiple points in the side chain is obtained by Michael addition reaction between the double bond of the thiol group and the acrylic acid.

[0023] As the diepoxy crosslinking agent (B), 1,4-butanediol diglycidyl ether, 1,2,7,8-diepoxyoctane, neopentyl glycol diglycidyl ether, etc. are preferably used, while as the transesterification catalyst (C), zinc acetate, triphenylphosphine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, etc. are preferably used.

[0024] The mixing ratio of the polyester resin raw material (A) and the diepoxy crosslinking agent (B) can be determined based on the functional group molar ratio between the side chain carboxylic acid of the polyester resin raw material (A) and the epoxy group of the diepoxy crosslinking agent (B). From the viewpoint of crosslinking reaction efficiency, the carboxylic acid group:epoxy group is preferably 1:0.5 to 1:1.5, more preferably 1:0.8 to 1:1.2. From the viewpoint of catalytic activity efficiency, the mixing ratio of the transesterification catalyst (C) to the free hydroxyl group is preferably 1:0.1 to 1:0.4, more preferably 1:0.15 to 1:0.3, in terms of the molar ratio of the free hydroxyl group:transesterification catalyst.

[0025] Regarding the conditions of the condensation polymerization reaction carried out in the preparation of the carboxylic acid group-containing polyester resin, from the viewpoint of uniform mixing of the constituent monomers and from the viewpoint of suppressing the coupling reaction between thiol groups during the condensation polymerization, 70°C to 120°C is preferable, and 80°C to 100°C is more preferable. From the viewpoint of obtaining a sufficiently high molecular weight substance, the reaction time is preferably 10 hours or more, and more preferably 20 hours or more. The molding method of the crosslinked product using the carboxylic acid group-containing polyester resin raw material obtained by the condensation polymerization and the subsequent Michael reaction, the diepoxy crosslinking agent, and the transesterification catalyst can be carried out using a Teflon (registered trademark) mold or a glass mold. In the crosslinking reaction, from the viewpoint of proceeding with sufficient crosslinking and preventing thermal decomposition of the sample, 120°C to 160°C and 4 hours or more are preferable.

[0026] The crosslinked polyester resin molded product may have various shapes, but is preferably in the form of a film from the viewpoint of maintaining a sufficient adhesive area. For example, the thickness of the film is preferably 0.1 mm to 3 mm from the viewpoint of the mechanical strength and surface smoothness of the resin sample.

[0027] FIG. 4 shows an embodiment in which (A) two crosslinked polyester resin films (20, 21) are laminated to form (B) a two-layer crosslinked polyester resin film (30). An adhesive layer (31) is formed by an ester exchange reaction in which the free hydroxyl groups contained in each of the crosslinked polyester resin films (20, 21) attack the C-0 bond of the ester bond of the crosslinked polyester resin film other than the crosslinked polyester resin film in which each of them is contained. The ester exchange reaction occurs due to an ester exchange catalyst present near the free hydroxyl groups and heating suitable for the catalytic action under pressure.

[0028] FIG. 5 shows a schematic diagram of the polyester exchange reaction between crosslinked polyester resins forming the adhesive layer (31A). The polymer main chains 1A and 1B and the covalent crosslinking portion 3A are contained in the same crosslinked polyester resin, and the polymer main chain 1C is contained in another same crosslinked polyester resin. The free OH group contained in the covalent crosslinking portion 3A attacks the C-0 bond of the polyester bond of the polymer main chain 1C under pressure due to the action of the transesterification catalyst. Then, the covalent crosslinking portion 3A and the polymer main chain 1C are bonded through the free 0 (oxygen atom), and a branched polymer main chain (the covalent crosslinking portion 3A is bonded to a part of the polymer main chain 1C) in which the covalent crosslinking portion 3A and the polymer main chain 1C are bonded is generated, and the adhesive layer 31A is formed. Meanwhile, the C-0 bond of the polyester bond of the polymer main chain 1C is cut to generate a polymer main chain end portion 1D whose end is a free OH group. It can be interpreted that the polymer main chain end portion 1D is also included in the adhesive layer 31A.

[0029] Regarding the manufacturing conditions of the multilayer crosslinked polyester resin film, the temperature is preferably 140°C to 200°C from the viewpoint of the bond exchange activation temperature and the heat resistance of the resin. The pressing pressure is preferably 100 Pa or more, more preferably 1 kPa or more, from the viewpoint of promoting bond exchange between the opposing surfaces. Also, in order to prevent the sample from breaking, it is preferably 100 MPa or less. The pressing time is preferably 2 hours, more preferably 4 hours, in order to obtain good adhesive strength, i.e., to obtain a sufficient number of molecular chains that have been bond exchanged across the opposing surfaces. EXAMPLES

[0030] (Preparation of polyester resin raw material) First, a polyester was synthesized by melt condensation polymerization of adipic acid, thiomalic acid, and 1,5-pentanediol. Then, a polyester resin material containing multiple carboxylic acid groups on the side chain was prepared by Michael addition between the thiol group of thiomalic acid and the double bond of acrylic acid. Table 1 shows the polyester resin material prepared. In Table 1, Code: PE-X / Y / Z is carboxylic acid-added thiomalic acid (X) / adipic acid (Y) / 1,5-pentanediol (Z), and N COOH is the number of carboxylic acid groups per polymer chain, and the COOH / Ester ratio is the ratio of carboxylic acid groups / ester bonds per polymer chain. X, Y, and Z represent the molar ratios of the constituent monomers in the polymer chain determined by 1H-NMR (see unit molar ratio).

[0031] [Table 1]

[0032] In Table 1, the number average molecular weight (Mn) and molecular weight distribution (PDI) were measured by GPC using a Shodex KD803 804 column, a Tosoh DP8020 pump system, and an RI detector (Tosoh RI-8020). The eluent used was DMF with LiBr (0.05 wt%) added.

[0033] (Crosslinked polyester resin film, Examples 1 to 6, Comparative Example 1) The crosslinked polyester resin film 22 shown in FIG. 8(A) was produced as follows. The polyester resin raw material 10, a diepoxy crosslinking agent (1,4-butanediol diglycidyl ether), and an ester exchange catalyst (zinc acetate) were each dissolved in chloroform. The solutions were mixed in a Teflon mold, and then the solvent was evaporated on a heater at 40°C. The mixed sample was heated under vacuum at 120°C for 4 hours to obtain a crosslinked resin. The obtained crosslinked resin was cut into a film shape with a width of 4 mm, a thickness of 0.3 mm, and a length of about 15 mm using a cutter (Example 1). Examples 2 and 3 were obtained in the same manner as Example 1, except that polyester resin raw materials 11 and 12 were used instead of polyester resin raw material 10. In Examples 1 to 3, the molar ratio of carboxylic acid:epoxy group was 1:1, and the proportion of the transesterification catalyst was 20 mol% relative to the free hydroxyl group.

[0034] Further, a crosslinked resin obtained in the same manner as in Example 1 using polyester resin raw material 10 was cut into a film shape using a cutter to have a width of 4 mm, a thickness of 0.15 mm, and a length of about 15 mm (Example 4). Examples 5 and 6 were obtained in the same manner as Example 4, except that polyester resin raw materials 11 and 12 were used instead of polyester resin raw material 10. In Examples 4 to 6, the molar ratio of carboxylic acid:epoxy group was 1:1, and the proportion of the transesterification catalyst was 20 mol% relative to the free hydroxyl group.

[0035] Further, the crosslinked resin obtained in the same manner as in Example 1, except that the polyester resin raw material 11 was used instead of the polyester resin raw material 10, was cut into a film shape using a cutter to obtain two crosslinked polyester resin films 22 (Example 7) with a width of 4 mm, a thickness of 0.5 mm, and a length of 25 mm. On the other hand, the crosslinked resin film of Example 7 was immersed in chloroform, which dissolves the transesterification catalyst well, to elute the transesterification catalyst, thereby producing a polyester resin film (Comparative Example 1) that does not contain the transesterification catalyst.

[0036] (Tensile test) A tensile test was carried out as follows using Examples 1 to 3. The results are shown in Table 2. Also, a chart showing the definitions of maximum stress and breaking elongation using Example 3 is shown in FIG. Measurements were performed at room temperature and a tensile speed of 10 mm / min using a SHIMADZU AG-X plus. Young's modulus (MPa) was calculated as stress (MPa) / displacement (%) from the stress at 5% deformation. Maximum stress (MPa) was calculated as the maximum stress measured up to breakage. Breaking elongation was calculated as the sample displacement (%) at breakage. The initial jig distance was approximately 15 mm. [Table 2]

[0037] From Table 2, it can be seen that the crosslinked polyester resin film obtained by this molecular design has sufficient flexibility at room temperature (elongation at break >> 20%), even though bond exchange crosslinking is introduced. In addition, because carboxylic acid groups are introduced at multiple points on the side chain, a Young's modulus sufficient for a flexible film was shown (>> 1 MPa). The Young's modulus tends to be higher for samples with a higher COOH / Ester ratio, suggesting that the crosslink density in the network structure can be controlled by the COOH / Ester ratio. In the above tensile test, from the viewpoint of maintaining strength and flexibility, the Young's modulus is preferably 0.10.1 MPa to 100 MPa, more preferably 1 MPa to 10 MPa, and the breaking elongation is preferably 10% to 500%, more preferably 30% to 200%, from the viewpoint of maintaining good stretchability.

[0038] As shown in FIG. 8(A), it was confirmed from Example 7 that it was transparent when picked up with tweezers 40.

[0039] As shown in Fig. 8(B), when both ends of Example 7 were bent 180° and brought together, it did not break, and when the bending force was released, it returned to its original state. This demonstrated that Example 7 had high strength and flexibility at room temperature. The fact that Example 7 had such high strength and flexibility at room temperature could also be estimated from the fact that the Tg (glass transition temperature) of Example 7 was about -30°C, which was significantly lower than room temperature.

[0040] (Softening properties) Using the samples of Examples 4 to 6, the softening properties were measured as follows. The softening temperature was determined as shown in FIG. 10 (in FIG. 10, L is the sample length during measurement, L 100℃ indicates the initial length of the sample at 100°C), and the results are shown in Table 3. Using a Hitachi TMA7100, the linear expansion coefficient was determined from the inflection point of the change in the linear expansion coefficient of the sample from room temperature to 230°C. The measurement was performed in a nitrogen gas atmosphere with a small constant tension (30 mN) applied to prevent the sample from bending. The initial distance between the jigs was about 15 mm.

[0041] [Table 3]

[0042] From Table 3, it can be seen that the crosslinked polyester resin into which the bond exchange type dynamic covalent crosslinking is introduced exhibits a unique softening characteristic at high temperatures. Ordinary amorphous crosslinked resins do not exhibit a softening point at high temperatures other than the glass transition temperature and decomposition temperature. Since the samples of Examples 4, 5, and 6 have a glass transition temperature of about -30°C and a decomposition temperature of 200°C or higher, it can be said that the above softening characteristic is due to the activation of bond exchange between ester bonds and free OH groups. In addition, the softening temperature is lower for samples with a higher COOH / Ester ratio. This is because the higher the COOH / Ester ratio, the higher the introduction rate of the "free OH group" which is the carrier of the ester exchange reaction, and the bond exchange is more likely to be activated at low temperatures. This result suggests that this polyester crosslinked resin can be controlled by the COOH / Ester ratio. In terms of the above softening characteristics, the softening temperature is preferably from 100°C to 250°C, more preferably from 120°C to 200°C, from the viewpoint of maintaining thermal stability and preventing thermal decomposition of the polymer chains.

[0043] (Two-layer crosslinked polyester resin film, Example 8, Comparative Example 2) Two sheets of Example 7 were used, and one end of each was overlapped as shown in Figure 8 (A) at a temperature of 140°C, a pressing pressure of 400 kPa, and a pressing time of 4 hours to produce a two-layer crosslinked polyester resin film 30 (Example 8) including a portion where sheets of Example 7 were bonded and laminated together. On the other hand, an attempt was made to produce a two-layer polyester resin film using two sheets of Comparative Example 1 in the same manner as in Example 7, but the Comparative Example 1 sheets did not adhere to each other, and a two-layer polyester resin film could not be produced (Comparative Example 2).

[0044] As shown in Fig. 9(A), when both ends of the two-layer crosslinked polyester resin film 30 were pinched and pulled, as shown in Fig. 9(B), the film did not break in the laminated portion 36, but broke in a portion other than the laminated portion 36, resulting in a multilayer crosslinked polyester resin film 35 with broken end portions. This revealed that the tensile strength of the two-layer portion 36, i.e., the adhesive portion, was high.

[0045] For example, a package can be made by forming a predetermined space between two sheets of crosslinked polyester resin in the form of a film, and bonding the crosslinked polyester resin together so that a useful object can be packed in the predetermined space.

[0046] (Remoldability, Example 9) Using Example 1 (FIG. 11), a deformation process was performed on Example 1 as shown in FIG. 12(A). That is, Example 1 was wrapped around a spatula 41, and both ends were secured to the spatula 41 with tape 42 to form a deformed crosslinked polyester resin film 23. The deformed crosslinked polyester resin film 23 was then subjected to a heat treatment process in which it was treated with heat. In the heat treatment process, the film was left at a high temperature (160°C) for 2 hours and allowed to cool to room temperature. After cooling, the deformed crosslinked polyester resin film 23 was removed from the spatula 41. Then, as shown in FIG. 12(B), the deformed crosslinked polyester resin film 23 became a reshaped crosslinked polyester resin film 24 in which the wrapped state was maintained (Example 9). It was presumed that the cross-linked polyester resin film was reformed because ester exchange was activated at high temperatures and a new equilibrium network structure was fixed during cooling.

[0047] In the heat treatment step, the temperature (high temperature) to which the deformed crosslinked polyester resin film is subjected is preferably 150° C. or higher, more preferably 170° C. or higher, from the viewpoint of bond exchange activation temperature, while it is preferably 200° C. or lower from the viewpoint of decomposition of polymer chains. The time for applying the temperature is preferably 1 hour or more, more preferably 2 hours or more, from the viewpoint of promoting sufficient bond exchange. The deformation of the crosslinked polyester resin film can be in various forms other than those described above, such as bending, rolling, compressing, stretching, etc.

[0048] (Scratch repair, Example 10) Example 1 (FIG. 11) was subjected to a process of making scratches 50 on its surface using a cutter (thickness of the cutter blade: 0.1 mm) as shown in FIG. 13(A). The scratches 50 were observed using a microscope on the surface of the crosslinked polyester resin film 25 including the scratches 50, and an image was obtained. The microscope observation was performed under conditions of a magnification of 20 times and a nitrogen atmosphere. From FIG. 13(A), it was confirmed that the length of the scratch 50 exceeded approximately 550 μm and that it had been cut into the surface by a cutter blade, and the depth of the scratch 50 was approximately 0.1 mm.

[0049] After the image was obtained, the crosslinked polyester resin film 25 was subjected to a heat treatment process in which the film was treated with heat. In the heat treatment process, the film was left at a high temperature (180°C) for 10 minutes and then cooled to room temperature. After the heat treatment process, the scratches 50 completely disappeared as shown in Fig. 13(B), and the crosslinked polyester resin film 26 was obtained with no scratches 50 on the surface (Example 10). It was presumed that the disappearance of the scratches, i.e., the scratch-repairing ability of the crosslinked polyester resin film, was due to the activation of bond exchange at high temperatures, which promoted the rearrangement of molecular chains near the surface.

[0050] In the heat treatment step, the temperature (high temperature) to which the scratched crosslinked polyester resin film is subjected is preferably 150° C. or higher, more preferably 170° C. or higher, from the viewpoint of bond exchange activation temperature. On the other hand, from the viewpoint of decomposition of polymer chains, it is preferably 200° C. or lower. Moreover, the time for which the temperature is applied is preferably 10 minutes or more, more preferably 20 minutes or more, from the viewpoint of sufficient bond exchange progression.

[0051] (Production of crosslinked polyester resin by immersion in transesterification catalyst solution) Fig. 14 shows an outline of a method for producing a crosslinked polyester resin by immersing a crosslinked polyester resin not containing a transesterification catalyst in a solution containing a transesterification catalyst. A molded product 9 made of a crosslinked polyester resin not containing a transesterification catalyst is immersed in a transesterification catalyst solution 60 for a certain period of time to obtain a molded product 8A made of a crosslinked polyester resin.

[0052] In FIG. 14, a molded product 9 is shown as a crosslinked polyester resin that does not contain a transesterification catalyst, but the molded product may have various shapes including a film shape. As the transesterification catalyst, zinc acetate or zinc acetylacetonate (II) salt is preferable from the viewpoint of solubility, and as the solution containing the transesterification catalyst, chloroform or tetrahydrofuran is preferable from the viewpoint of solubility and volatility. When the transesterification catalyst is zinc acetate and the solution is chloroform, the zinc acetate is dissolved in chloroform, and such a dissolved state is preferable from the viewpoint of the degree of penetration into the sample. On the other hand, from the viewpoint of catalytic activity, the transesterification catalyst may be in a dispersed state in the solution.

[0053] The concentration of the transesterification catalyst is preferably 1.0 mg / mL or more, more preferably 2.5 mg / mL or more, from the viewpoint of catalytic activity. Also, from the viewpoint of solubility in the solvent, it is preferably 20 mg / mL or less, more preferably 10 mg / mL or less. The time for immersing the crosslinked polyester resin not containing the transesterification catalyst in the transesterification catalyst solution is preferably 6 hours or more, more preferably 12 hours or more, from the viewpoint of equilibrium swelling degree.

[0054] (Crosslinked resin (film-like piece) not containing transesterification catalyst, Reference Comparative Examples 1 to 4) The polyester resin raw material 10 and diepoxy crosslinking agent (1,4-butanediol diglycidyl ether) were dissolved in chloroform. The solutions were mixed in a Teflon mold, and then the solvent was evaporated on a heater at 40°C. The mixed sample was heated at 120°C for 4 hours under vacuum to obtain a crosslinked resin not containing an ester exchange catalyst. The obtained crosslinked resin not containing an ester exchange catalyst was cut into a film shape using a cutter, and four sheets (Reference Comparative Examples 1 to 4) were obtained with a width of 4 mm, a thickness of 0.3 mm, and a length of about 15 mm. In Reference Comparative Examples 1 to 4, the molar ratio of carboxylic acid to epoxy group was 1:1.

[0055] (Crosslinked polyester resin (film-like piece), Comparative Example 3, Examples 11 to 13) Each of the film pieces of Reference Comparative Examples 1 to 4 was immersed for 12 hours in chloroform solutions with zinc acetate concentrations of 0 mg / mL, 2.5 mg / mL, 5 mg / mL, and 10 mg / mL to obtain film pieces of crosslinked polyester resin (Comparative Example 3, Examples 11 to 13). Linear expansion coefficients were measured for Comparative Example 3 (zinc acetate concentration: 0 mg / mL), Example 11 (zinc acetate concentration: 2.5 mg / mL), Example 12 (zinc acetate concentration: 5 mg / mL), and Example 13 (zinc acetate concentration: 10 mg / mL).

[0056] (Linear expansion coefficient measurement) The linear expansion coefficient was measured by increasing the temperature (100℃ to 200℃) with a constant weak stress (30mN) on a film piece and measuring the change in sample length of the film piece. The measurement results are plotted as follows: temperature on the horizontal axis and L (film length) / film length at 100℃ on the vertical axis. 100℃ (film length at 100° C.) is shown in FIG. 15, it was found that in Examples 11 to 13, the sample length increased rapidly at high temperatures, i.e., the sample softened, and the degree of the increase increased from Example 11 to Example 13, i.e., as the zinc acetate concentration increased. It was presumed that this tendency to increase was due to the activation of transesterification at high temperatures.

[0057] (Softening temperature) Fig. 16 was created based on Fig. 15. That is, when the difference (ΔLexp-const) between the actual sample length change (solid line in Fig. 15) and the constant sample length change (dotted line in Fig. 15) was calculated, and the softening temperature (dotted line in Fig. 15) defined as this difference = 0.005 was calculated, it was found that the softening temperature decreased from Example 11 to 13, that is, as the zinc acetate concentration increased. This softening provides the crosslinked polyester resin with remoldability and reprocessability, which is advantageous for, for example, thinning of films and fine processing of crosslinked resins. [Industrial Applicability]

[0058] It can be utilized as a crosslinked polyester resin that forms a package that can define a predetermined space and can encase a useful object in the predetermined space. [Explanation of symbols]

[0059] 1, 1A, 1B, 1C, 1D: Polymer main chain 2: Ester bond 3, 3A: Covalent crosslinking moiety 4: Free OH group (hydroxyl group) 5: Polyester resin 6, 6A: Transesterification catalyst 7: Cross-linked polyester resin 8: Molded products made from cross-linked polyester resin 8A: Molded product made of cross-linked polyester resin 9: Molded products made from cross-linked polyester resin that does not contain an ester exchange catalyst 10, 11, 12: Polyester resin raw material 20, 21, 22: Cross-linked polyester resin film 23: Deformed cross-linked polyester resin film 24: Reformed cross-linked polyester resin film 25: Cross-linked polyester resin film with scratches on the surface 26: Cross-linked polyester resin film with surface scratches disappeared after heat treatment 30: 2-layer cross-linked polyester resin film 31, 31A: Adhesive layer 35: Two-layer cross-linked polyester resin film with broken edge 36: Laminated (2 layer) part 40: Tweezers 41: Spatula 42: Tape 50: Scar 60: Transesterification catalyst solution

Claims

1. A crosslinked polyester resin comprising a polyester resin obtained by crosslinking a polyester resin raw material containing ester bonds and carboxylic acid groups at multiple points and in which the ratio of the carboxylic acid groups to the ester bonds is 10 mol % to 50 mol % with a diepoxy crosslinking agent, and an ester exchange catalyst.

2. 2. The crosslinked polyester resin according to claim 1, wherein the number average molecular weight of the polyester resin raw material is 8,000 or more, and the number of polyester bonds contained in the polyester resin raw material is 100 or more.

3. A crosslinked polyester resin as described in claim 1 or 2, wherein the ratio of carboxylic acid groups in the polyester resin raw material to epoxy groups in the diepoxy crosslinking agent (carboxylic acid groups:epoxy groups) is 1:0.5 to 1:1.

5.

4. The crosslinked polyester resin according to any one of claims 1 to 3, which is in the form of a film.

5. A multi-layer crosslinked polyester resin film comprising a portion in which the film-shaped crosslinked polyester resin according to claim 4 is bonded and laminated.

6. A packaging material comprising at least a part of the multilayer crosslinked polyester resin film according to claim 5.

Citation Information

Patent Citations

  • Heattsensitive carboxylated copolymer adhesive and its production method

    JP1977005849A

  • Coating composition for coated steel sheet

    JP1990142869A

  • Method for producing modified polyester resin

    JP1995304844A

  • Self-restorative resin composition, part for lighting equipment and lighting equipment using the resin composition

    JP2005023166A

  • Self-repairing resin body, self-repairing structure, method for producing self-repairing resin body, and material for forming self-repairing resin body

    JP2010260979A